2016
DOI: 10.1200/jgo.2015.001040
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Burden at the Uganda Cancer Institute

Abstract: PurposeIn Uganda, the incidence of prostate cancer is increasing at a rate of 5.2% annually. Data describing presentation and outcomes for patients with prostate cancer are lacking.MethodsA retrospective review of medical records for men with histologically confirmed prostate cancer at the Uganda Cancer Institute (UCI) from January 1 to December 17, 2012, was performed.ResultsOur sample included 182 men whose mean age was 69.5 years (standard deviation, 9.0 years). Patients who presented to the UCI had lower u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
(11 reference statements)
3
28
0
Order By: Relevance
“…Related studies in Uganda and other developing countries have found other possible causes of patient and health system delays to include patients non-adherence to the recommended investigations, referral complexity as cancer investigations are done from different locations and lack of large scale population-based prostate cancer screening (5,10,19). Indeed, in our cohort all patients were assessed for prostate cancer after developing symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Related studies in Uganda and other developing countries have found other possible causes of patient and health system delays to include patients non-adherence to the recommended investigations, referral complexity as cancer investigations are done from different locations and lack of large scale population-based prostate cancer screening (5,10,19). Indeed, in our cohort all patients were assessed for prostate cancer after developing symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…In Uganda prostate cancer has been increasing at a rate of 5.2% annually, making it the most rapidly increasing cancer in the country and in sub-Saharan Africa (5). Despite the increase in incidence, approximately 90% of prostate cancer patients are not aware of the disease and as a result they do not take early urinary symptoms seriously hence they are diagnosed late with very advanced disease in stage IV presenting with incurable tumors (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…The Globocan report of 2018 indicates that Uganda had 2086 (6.4%) incident cases of prostate cancer, and this was the second most common cancer in males [ 1 ]. In Uganda, more than 90% of all the prostate cancer cases seen at the UCI are referrals from the region, and these often present with advanced disease [ 10 ]. Few studies in sub-Saharan Africa have described the clinical and demographic patterns of prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda prostate cancer has been increasing at a rate of 5.2% annually, making it the most rapidly increasing cancer in the country and in sub-Saharan Africa (5). Despite the increase in incidence, approximately 90% of prostate cancer patients are not aware of the disease and as a result they do not take early urinary symptoms seriously hence they are diagnosed late with very advanced disease in stage IV presenting with incurable tumors (5)(6)(7). Late diagnosis limits treatment options, increases mortality and leads to low quality of life for patients and their families (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies in low and middle income countries also found an association between delays and late diagnosis among cancer patients(16,17). Such late diagnosis results into poor prognosis and death(18).Related studies in Uganda and other developing countries have found other possible causes of patient and health system delays to include patients non-adherence to the recommended investigations, referral complexity as cancer investigations are done from different locations and lack of large scale population-based prostate cancer screening(5,10,19). Indeed, in our cohort all patients were assessed for prostate cancer after developing symptoms.…”
mentioning
confidence: 99%